NADiA ProsVue prostate-specific antigen slope is an independent prognostic marker for identifying men at reduced risk of clinical recurrence of prostate cancer after radical prostatectomy. - Moul, J; Lilja, H; Semmes, O; Lance, R; Vessella, R; Fleisher, M; Mazzola, C; Sarno, M; Stevens, B; Klem, R; McDermed, J; Triebell, M; et al. (2012)
OBJECTIVE: To validate the hypothesis that men displaying serum prostate-specific antigen (PSA) slopes ≤ 2.0 pg/mL/mo after prostatectomy, measured using a new immuno-polymerase chain reaction diagnostic test (NADiA ProsVue), have a reduced risk of clinical recurrence as determined by positive biopsy, imaging findings, or death from prostate cancer. MATERIALS AND METHODS: From 4 clinical sites, we selected a cohort of 304 men who had been followed up for 17.6 years after prostatectomy for clinical recurrence. We assessed the prognostic value of a PSA slope cutpoint of 2.0 pg/mL/mo against established risk factors to identify men at low risk of clinical recurrence using uni- and multivariate Cox proportional hazards regression and Kaplan-Meier analyses. RESULTS: The univariate hazard ratio of a PSA slope >2.0 pg/mL/mo was 18.3 (95% confidence interval 10.6-31.8) compared with a slope ≤ 2.0 pg/mL/mo (P <.0001). The median disease-free survival interval was 4.8 years vs >10 years in the 2 groups (P <.0001). The multivariate hazard ratio for PSA slope with the covariates of preprostatectomy PSA, pathologic stage, and Gleason score was 9.8 (95% confidence interval 5.4-17.8), an 89.8% risk reduction for men with PSA slopes ≤ 2.0 pg/mL/mo (P <.0001). The Gleason score (<7 vs ≥ 7) was the only other significant predictor (hazard ratio 5.4, 95% confidence interval 2.1-13.8, P = .0004). CONCLUSION: Clinical recurrence after radical prostatectomy is difficult to predict using established risk factors. We have demonstrated that a NADiA ProsVue PSA slope of ≤ 2.0 pg/mL/mo after prostatectomy is prognostic for a reduced risk of prostate cancer recurrence and adds predictive power to the established risk factors.